Encyclopedia of Life Sciences 2012
DOI: 10.1002/9780470015902.a0000601.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes: Irreversible Inhibition

Abstract: Many drugs that are in clinical use work by irreversibly inhibiting specific enzymes, either in the individual being treated or in an invading organism. Enzyme inhibitors are also of value for understanding the behaviour of individual enzymes and metabolic systems. Recovery from irreversible inhibition requires the synthesis of new enzyme. Although those irreversible inhibitors that react with specific groups in the enzyme protein generally inhibit more than one enzyme, those that initially form a noncovalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…We addressed this inconsistency by specifically assessing the ␤-glucosidase activity of GBA2 for its sensitivity to inhibition by CBE, using membrane preparations that are devoid of GBA. We found that GBA2 is inactivated by CBE, in a time-dependent fashion, which is typical for mechanism-based enzyme inhibitors (80,81). Measurement of K I and k inact values showed that CBE bound GBA2 with less affinity and that CBE inactivated GBA2 at a lower rate, as compared with the interaction of CBE and GBA.…”
Section: Discussionmentioning
confidence: 58%
“…We addressed this inconsistency by specifically assessing the ␤-glucosidase activity of GBA2 for its sensitivity to inhibition by CBE, using membrane preparations that are devoid of GBA. We found that GBA2 is inactivated by CBE, in a time-dependent fashion, which is typical for mechanism-based enzyme inhibitors (80,81). Measurement of K I and k inact values showed that CBE bound GBA2 with less affinity and that CBE inactivated GBA2 at a lower rate, as compared with the interaction of CBE and GBA.…”
Section: Discussionmentioning
confidence: 58%
“…Other propargylamine inactivators similarly form adducts at N5 of the FAD, including clorgyline [ 16 ], selegiline [ 16 ] and rasagiline [ 17 ], and two compounds examined in this work, ASS234 [ 18 ] and F2MPA [ 19 ]. Formation of the adducts can be measured as the time-dependent onset of inhibition not reversed by dialysis [ 20 ] and directly observed by changes in the spectrum of the FAD cofactor [ 11 , 18 ]. The irreversible inhibition by these compounds involves activation by MAO to give an allenyl imine product that reacts chemically to form a covalent bond to the flavin prosthetic group [ 11 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Irreversible inhibitors that irreversibly binds the protein. In this case, the recovery of enzymatic functions does occur with the physiological turn-over [89], and their ability to closely tie their target results in a prolonged therapeutic response with a consequent decrease in doses and frequency of administration, and a significantly increased patient compliance [90]. Obviously, they also have disadvantages, such as episodes of toxicity and hypersensitivity [87,91].…”
Section: Strategies For the Development Of Small Molecule Rdrp Inhibimentioning
confidence: 99%